Design, synthesis, and biological evaluation of water-soluble amino acid prodrug conjugates derived from combretastatin, dihydronaphthalene, and benzosuberene-based parent vascular disrupting agents. Issue 5 (1st March 2016) - Devkota, Laxman; Lin, Chen-Ming; Strecker, Tracy E.; Wang, Yifan; Tidmore, Justin K.; Chen, Zhi; Guddneppanavar, Rajsekhar; Jelinek, Christopher J.; Lopez, Ramona; Liu, Li; Hamel, Ernest; Mason, Ralph P.; et al.
Graphical abstract: Abstract: Targeting tumor vasculature represents an intriguing therapeutic strategy in the treatment of cancer. In an effort to discover new vascular disrupting agents with improved water solubility and potentially greater bioavailability, various amino acid prodrug conjugates (AAPCs) of potent amino combretastatin, amino dihydronaphthalene, and amino benzosuberene analogs were synthesized along with their corresponding water-soluble hydrochloride salts. These compounds were evaluated for their ability to inhibit tubulin polymerization and for their cytotoxicity against selected human cancer cell lines. The amino-based parent anticancer agents7, 8, 32 (also referred to as KGP05) and33 (also referred to as KGP156) demonstrated potent cytotoxicity (GI50 = 0.11–40 nM) across all evaluated cell lines, and they were strong inhibitors of tubulin polymerization (IC50 = 0.62–1.5 μM). The various prodrug conjugates and their corresponding salts were investigated for cleavage by the enzyme leucine aminopeptidase (LAP). Four of the glycine water-soluble AAPCs (16, 18, 44 and45 ) showed quantitative cleavage by LAP, resulting in the release of the highly cytotoxic parent drug, whereas partial cleavage (<10–90%) was observed for other prodrugs (15, 17, 24, 38 and39 ). Eight of the nineteen AAPCs (13 –16, 42 –45 ) showed significant cytotoxicity against selected human cancer cell lines. The previously reported CA1-diamine analog and its corresponding hydrochloride salt (8 and10, respectively) caused extensive disruption (at a concentration of 1.0 μM) of human umbilical vein endothelial cells growing in a two-dimensional tubular network on matrigel. In addition, compound10 exhibited pronounced reduction in bioluminescence (greater than 95% compared to saline control) in a tumor bearing (MDA-MB-231-luc) SCID mouse model 2 h post treatment (80 mg/kg), with similar results observed upon treatment (15 mg/kg) with the glycine amino-dihydronaphthalene AAPC (compound44 ). Collectively, these results support the further pre-clinical development of the most active members of this structurally diverse collection of water-soluble prodrugs as promising anticancer agents functioning through a mechanism involving vascular disruption.